2020
DOI: 10.1175/wcas-d-19-0074.1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Weather Forecast Inconsistency on User Trust

Abstract: For high-impact weather events, forecasts often start days in advance. Forecasters believe that consistency among subsequent forecasts is important to user trust and can be reluctant to make changes when newer, potentially more accurate information becomes available. However, to date, there is little empirical evidence for an effect of inconsistency among weather forecasts on user trust, although the reduction in trust due to inaccuracy is well documented. The experimental studies reported here compared the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…results indicate for designing public forecast maps (Seipel and Lim, 2017;Correll et al, 2018). In contrast, other experimental literature on uncertainty communication (e.g., Burgeno and Joslyn (2020); Joslyn and LeClerc (2012); Van Der Bles et al…”
Section: Evaluating the Effectiveness Of Uncertainty Visualizationsmentioning
confidence: 65%
“…results indicate for designing public forecast maps (Seipel and Lim, 2017;Correll et al, 2018). In contrast, other experimental literature on uncertainty communication (e.g., Burgeno and Joslyn (2020); Joslyn and LeClerc (2012); Van Der Bles et al…”
Section: Evaluating the Effectiveness Of Uncertainty Visualizationsmentioning
confidence: 65%
“…While a growing body of research suggests that addressing uncertainty in forecasts effectively builds end‐user trust (Burgeno & Joslyn, 2020; Joslyn & Grounds, 2015; Joslyn & LeClerc, 2012; LeClerc & Joslyn, 2015), ‘Sharpiegate’ inadvertently reflects concerns that meteorologists frequently raise regarding probabilistic forecast communication (i.e., that end‐users may ignore a large body of evidence indicating risks are high, instead favouring a minority view that risks are low). Former‐President Trump's ad hoc extension of Hurricane Dorian's track into Alabama represents an inverse of meteorologists' concern (i.e., an overstatement of very minimal risk).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, many end-users were aware of the shifting messaging around Hurricane Dorian's intensity. This inconsistency seemed to convey a sense of uncertainty (e.g., Burgeno & Joslyn, 2020) that adjusted end-users' expectations. This supports suggestions that probabilistic forecast information may be a better strategy for communicating information to the public and building end-user trust.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the outcome is expected for participants who choose to predict the protagonist’s action and are more likely to have a positive perception. It is well known that when the outcome of a weather forecast is not consistent with the actual weather, the trust in that forecast is reduced [ 38 , 39 ]. It can thus be suggested that the expected outcome might contribute to a positive perception of the whereabouts initiative.…”
Section: Discussionmentioning
confidence: 99%